Structural effects on glass stability and crystallization. Issue 16 (3rd April 2018) - Rodrigues, A. M.; Silva, L. D.; Zhang, R.; Soares, V. O.
Abstract : We report the correlation between glass stability, crystallization activation energy and the glass structure to one pure devitrite glass (Na2 Ca3 Si6 O16 ), and two other glasses in which 4 mol% and 8 mol% of devitrite glass were replaced with TiO2 (Dev, 4Ti and 8Ti, respectively). Abstract : Herein, glass stability and crystallization activation energy ( E c ) were evaluated in a pure devitrite glass (Na2 Ca3 Si6 O16 ) and two other glasses (Dev, 4Ti, and 8Ti, respectively) in which 4 mol% and 8 mol% of devitrite glass was replaced with TiO2 . The results were in agreement with those of glass structure studies reported in the literature. Glass stability parameters were calculated from DSC experiments using the equations K 2 = T x − T g and K M = ( T x − T g ) 2 / T g . It was observed that for all equations, the glass stability values increased with the addition of TiO2 contents. This behavior was due to the following two factors: a decrease in the glass modifier concentrations (Na + and Ca 2+ ) and Ti ions added on the glass network, acting as glass formers, in which Si–O–Si were replaced with Si–O–Ti 4+ tetrahedrons. Isothermal heat treatments were carried out at 800 °C, and it was verified by scanning electron microscopy that TiO2 did not act as a nucleating agent in Na2 Ca3 Si6 O16 and surface crystallization was predominant for all glasses studied herein. The Kissinger equation was used to obtain the crystallization activation energy ( E c ); it was observed that the E c values decreased with the addition of TiO2, and this behavior was explained regarding the bond energy dissociation (Si–O and Ti–O) and the calculated viscosity data.